Bone-eating Osedax worms (Annelida: Siboglinidae) regulate biodiversity of deep-sea whale-fall communities. (December 2017) - Alfaro-Lucas, Joan M.; Shimabukuro, Maurício; Ferreira, Giulia D.; Kitazato, Hiroshi; Fujiwara, Yoshihiro; Sumida, Paulo Y.G.
Abstract: Although it is well recognized the capital role of "bone-eating" Osedax worms in the degradation of vertebrate skeletons in the deep sea, very little is known about their effects on bone faunal assemblages. Here we aim to shed light on the bone colonization process and determine 1) whether Osedax degradation induces different bone epi/infaunal assemblages and 2) how biodiversity is affected by Osedax colonization. We describe and compare the epi/infaunal assemblage structures of caudal vertebrae colonized and not colonized by Osedax of an abyssal juvenile whale carcass serendipitously found at 4204 m depth in the SW Atlantic Ocean by HOV Shinkai 6500 . Our results show that whale skeletons are very heterogeneous habitats that harbor specific and very rich assemblages and that contrasting epi/infaunal community patterns are found depending on the presence of Osedax . Vertebrae not colonized by Osedax were both well preserved and in a highly sulfophilic stage with chemosynthetic bacterial mats and numerous epifaunal organisms that fed on them. On the contrary, vertebrae colonized by Osedax were heavily degraded and did not exhibit evidence of a sulfophilic stage, harboring a distinct epifaunal assemblage. In general, bone infaunal assemblages were dominated by nematodes, especially in vertebrae without Osedax (ca. 77%) where organisms were only found in bone outer layers, showing a colonization pattern similar to that described for bacteria. Infauna in Osedax -colonized bones were present throughout the inner-matrices and were on average three times more abundant (ca. 1800 ind. 100 cm −3 ) and twice as rich in number of species (16 species). Here, bones had a relatively higher proportion of the polychaete Capitella iatapiuna (ca. 39%) in comparison with nematodes (ca. 52%). Besides, a higher number of rare species were present in bones with Osedax . We suggest that Osedax degradation increases water diffusion through matrices probably modifying reduced-compound fluxes and truncating the sulfophilic stage. Furthermore, it is likely that larger and distinct infaunal biodiversity is a result of an increase in bone structural complexity caused by Osedax, which also facilitates the colonization of inner-bone matrices. We conclude that Osedax is an important ecosystem engineer that enhances biodiversity in deep-sea whale-fall communities.